Peritonitis with small intestinal perforation caused by a plastic bread bag clip: A case report. (2018) - Mitsui, Ema; Inaba, Mototaka; Mimura, Tetsushige
Highlights: Ingested plastic bread bag clips can cause serious adverse events like gastrointestinal perforation and penetration. Bread bag clips need caution in handling not to be ingested. In cases of accidental ingestion of bread bag clips careful observations should be made. Abstract: Introduction: Cases of a foreign body ingestion often require surgical treatment due to perforation or penetration. There is a possibility that plastic bread bag clips also cause serious adverse events when they are ingested. Presentation of a case: We report a rare case of peritonitis with small intestinal perforation caused by a plastic bread bag clip that needed surgical treatment. A 47-year-old man was taken to our hospital because of abdominal distension and vomiting. A computed tomography test demonstrated findings of small intestinal perforation, and a high-density object was seen in the jejunum. During emergency surgery, it was discovered that a plastic bread bag clip had caused the perforation. Discussion: Some cases of gastrointestinal tract perforation or bleeding due to the ingestion of bread bag clips have been reported overseas. Because bread bag clips are normally radiolucent, they are impossible to discover when accidentally ingested, so diagnosis is difficult unless the patient remembers the incident. The shape of plastic bread bag clips is unique and can result in a trap-like effect, which prevents easy removal once ingested. Conclusion: Bread bag clips need caution in handling, and in cases of accidental ingestion, careful observations should be made to allow for removal within reach of upper GI endoscopy. The following case report has been reported in line with the SCARE criteria [1 ].